L’abandon aux études doctorales : un problème de direction? - Constance Denis; Christelle Lison (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
When perusing the literature, we often stumble on the fact that one doctoral student out of two will quit his/her studies. How do we meet this? Should we be alarmed by such a high rate of attrition? Is quitting a bad thing in itself? Maybe it indicates alternative pathways. Is it realistic or even desirable that all doctoral students complete their studies? Whatever the answers to these questions, it is generally admitted that supervision plays an important role in supporting study persistence; 1) guided admission, from the early stages, helps prevent some dropping out, 2) transparent communication, when dealing with the inevitable times of feeling bereft, impacts on perseverance, 3) ongoing work around employability helps identify concrete goals and work on next steps. This paper investigates pedagogical practices that specifically address the relationship between supervision and perseverance in doctoral studies. It is informed by the results of a research carried out with 20 doctoral students and 20 supervisors on their experiences within doctoral supervision. Questions and reflections punctuate this article in a way that provides a scientific and pragmatic perspective while acknowledging the work that still needs to be done to value doctoral supervision and its limitations.